Manajemen Konflik Pada Franchise Roti Bakar Gandaria Magetan - Rendra Firmansyah; Luhur Prasetiyo (Niqosiya: Journal of Economics and Business Research, 2023)
Conflict is common in everyday life, including business. Conflicts occur between franchisors and franchisees in the Roti Bakar Gandaria Magetan franchise. Conflicts arise due to policies that need to be carried out correctly and services that are not optimal. For this reason, this study was conducted to determine how conflict management was carried out by the Roti Bakar Gandaria franchise head and its impact. The method used in this study is qualitative, with data collection techniques in the form of interviews and conservation with franchisors and franchisees who experience conflict. The data analysis technique used is a deductive analysis that departs from general to specific by looking at the theory and then colliding with actual conditions. The results of this study show that the conflict in the Gandaria Toast franchise is constructive-horizontal. The leading cause of conflict is poor communication between franchisors and franchisees. The strategies to resolve conflicts are Collaboration Strategy, Competitive Strategy (competing), and Accommodative Strategy. The impact after the franchisor issues a policy to the franchisee is the resolution of the conflict, even though the franchisee is dissatisfied because the decision issued is considered inappropriate.